Programs to improve body image in adolescents: A systematic review - Flores Perez, Virginia; Camacho Ruiz, Esteban Jaime; Escoto Ponce de León, María del Consuelo; Cervantes Luna, Brenda Sarahi; Ibarra Espinosa, Manuel Leonardo (Horizonte Sanitario, 2023)
Objective: To examine the intervention programs that have been conducted on body image in adolescents. Materials and methods: The PRISMA statement was used in this review. The search for studies was conducted in PubMed, Web of Science, MEDLINE-ProQuest, and EBSCO databases from January 1, 2017, to January 25, 2022. Methodological quality was assessed using the Quality Assessment Tool for Quantitative Studies, developed by the Effective Public Health Practice Project. Results: Eight studies were included, most of which had a strong methodological quality. The results obtained after the implementation of the programs reflected favorable changes in body image and body satisfaction for adolescents between 11 and 18 years old, only for five studies. Additionally, five studies maintained the same changes at follow-up. Conclusions: Findings from this review allow us to conclude that intervention programs are a safe and effective way to influence adolescent body image. Keywords: Body image; Body dissatisfaction; Adolescents; Program evaluation; Health promotion.